Las técnicas grafo plásticas y la creatividad en los niños de 4 a 5 años de la Escuela de Educación Básica Filomena Mora de Carrión de la ciudad de Loja, periodo académico 2022-2023. - Soto Cumbicus, Olga del Carmen (2023)
Creativity is the ability to generate new ideas, novel solutions, express themselves in a unique way by developing their creative thinking, to solve problems presented when interacting with their peers in their immediate environment. The general objective was to determ ine the use of grapho-plastic techniques to strengthen creativity in children from 4 to 5 years of age at Filomena Mora de Carrión Basic Education School in 2022-2023 academic period. The study covered the quasi-experimental design, having a mixed approach with the purpose of obtaining quantitative and qualitative data, in the same way the descriptive scope was used to know the population with which we worked; as for the methods I consider both the inductive-deductive in the conclusions and the analytical-synthetic in the collection of information of the theoretical framework. On the other hand, the instrument used was the adaptation of the Torrance test, which evaluates children's creative thinking through the components of fluency, flexibility and originality. The results obtained in the pre-test were in the low level with 69.73%, in the medium level with 19.92%, while in the high level with 10.35%, having difficulties in the expression of ideas, flexibility to new events, little originality in their work, and after the intervention the results were in the low level with 27.53%, in the medium level with 34.13%, and in the high level with 38.13%, reducing the difficulties mentioned above. It is concluded that the grapho-plastic techniques used in an adequate manner strengthen the creativity of the children, helping them to be authentic, expressive and managing a better development in the resolution of conflicts in their daily coexistence, improving their quality of life. Key words: Imagination, Creative thinking, Graphic-plastic techniques, Creativity blocks.